Skin-inspired, fully autonomous self-warning and self-repairing polymeric material under damaging events - Zhang, He (2021)
Polymers are susceptible to small damage which is difficult to detect and repair and may lead to catastrophic failure if left unattended at the early stage. How to autonomously warn and repair the damage simultaneously is a promising yet challenging task, owing to the difficulty in integrating different functional elements for packaging and lack of suitable vehicles to carry a multirole trigger with high reactivity. Herein, inspired by human skin in the damage-healing process, we report a genuinely fully autonomous smart material that is capable of warning of and healing damage via simply incorporating dual microcapsules containing polyamine as a multirole trigger and epoxy monomer dyed with a pH indicator, respectively. Both microscopic "subcutaneous" damage and macroscopic surface damage can be warned of by a conspicuous red color, not only rapidly upon occurrence but also permanently after being repaired. Accompanied with the comprehensive warning, the smart material shows high healing performance upon dynamic impact damage with efficiency up to 100% without external interventions. This facile and ready strategy with fully autonomous warning and healing functions independent of the host matrix provides a new avenue to enhance the reliability and longevity of a wide variety of polymeric materials ranging from functional coatings to structural composites.